Pre-exposure Prophylaxis Awareness and Endorsement among Adolescents and Young Adults in Tanzania: Insights from the 2022 Demographic and Health Survey - Alpha Johnson Kapola; Rahma Musoke; Glenda Marie Manayon; Hassan Fredrick Fussi; Hafidha Mhando Bakari; Haji Mbwana Ally; Swalehe Mustafa Salim; Zuhura Mbwana Ally; Lynn Moshi; Mariam Salim Mbwana; Habib Omari Ramadhani (Annals of Global Health)
Background: Pre-exposure prophylaxis (PrEP) is an effective measure for preventing human immunodeficiency virus (HIV) infection among people at risk, including adolescents and young adults (AYA). Objectives: This study evaluates the prevalence of PrEP awareness and endorsement, as well as the factors associated with these outcomes, using data from the 2022 Tanzania Demographic and Health Survey. Methods: The analysis included participants aged 15–24 years. Participants were asked whether they had ever heard of daily medication to prevent HIV (PrEP) and whether they approved of daily PrEP use. Demographic characteristics and HIV testing information were also collected. Logistic regression models were used to assess factors associated with PrEP awareness and endorsement, and the weighted prevalence of these outcomes was calculated. Findings: A total of 8,268 respondents aged 15–24 years were evaluated, of whom 5,852 (70.9%) were female. Overall, the prevalence of PrEP awareness and endorsement was 6.9% (95% confidence interval [CI] 6.2–7.7) and 5.7% (95% CI 5.1–6.4), respectively. Female respondents (adjusted odds ratio [aOR] = 0.69; 95% CI 0.51–0.91) and rural residents (aOR = 0.78; 95% CI 0.61–1.00) had lower odds of PrEP awareness compared with male respondents and urban residents, respectively. Previously, HIV testing and receiving test results (aOR = 2.00; 95% CI 1.50–2.66) and an age of 20–24 years versus 15–19 years (aOR = 1.54; 95% CI 1.20–1.96) were associated with increased odds of PrEP awareness. The odds of AYA endorsement of PrEP were higher among those aged 20–24 years versus 15–19 years (aOR = 1.39; 95% CI 1.07–1.83) and those who previously tested for HIV and received results (aOR = 1.97; 95% CI 1.43–2.72), but lower among female respondents (aOR = 0.66; 95% CI 0.49–0.88). Conclusion: PrEP awareness and endorsement among AYA in Tanzania were low, with nearly 7 in 100 aware of PrEP and 6 in 100 approving of its use. Targeted interventions focused on adolescents, females, and rural communities are needed to increase PrEP awareness and usage to achieve the Joint United Nations Programme on HIV/Acquired Immune Deficiency Syndrome (AIDS) (UNAIDS) 95–95–95 goals for HIV epidemic control.